1985
DOI: 10.1254/jjp.39.153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bifemelane Hydrochloride (MCI-2016) on Experimental Amnesia (Passive Avoidance Failure) in Rodents

Abstract: Abstract-To further predict the possible activity on memory disorders, the effect of MCI-2016 (bifemelane hydrochloride) was examined using the passive avoidance (PAR) failure technique as an experimental model of amnesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 16 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In addition, noradrenaline re-uptake inhibition (Egawa et al., 1983) and monoamine oxidase inhibition (Naoi et al, 1988) have been described. It shows antiamnestic effects in rats and mice ( Ogawa et al, 1988a;Tobe et al, 1985) and elicits transcallosal responses in rats (Okuyama and Aihara, 1988). Bifemelane significantly inhibits the ischemia-induced depletion of acetylcholine in cerebral cortex, hippocampus and striatum of gerbils (Ogawa et al, 1988b).…”
Section: Cerebrai Metabolie Enhaneers (Fig 8)mentioning
confidence: 99%
“…In addition, noradrenaline re-uptake inhibition (Egawa et al., 1983) and monoamine oxidase inhibition (Naoi et al, 1988) have been described. It shows antiamnestic effects in rats and mice ( Ogawa et al, 1988a;Tobe et al, 1985) and elicits transcallosal responses in rats (Okuyama and Aihara, 1988). Bifemelane significantly inhibits the ischemia-induced depletion of acetylcholine in cerebral cortex, hippocampus and striatum of gerbils (Ogawa et al, 1988b).…”
Section: Cerebrai Metabolie Enhaneers (Fig 8)mentioning
confidence: 99%
“…From these results, bifemelane might cause an improvement of muscarinic re ceptors impaired in the hippocampus of SAM P/8. Recently, it has been reported that bifemelane hydrochloride suppressed the de crease in ACh concentration in the cerebral cortex and hippocampus of ischemic gerbils (10), the decrease in [3H]QNB binding in the hippocampus of aging rats, and decreases in learning and memory activities of scopolamine treated rats (11). Furthermore, bifemelane hydrochloride augments the long-term poten tiation in guinea pig hippocampal slices (12) through possible activation of protein kinase C (13), but the effect of this drug is inhibited by scopolamine.…”
mentioning
confidence: 99%